PREMIUM PRICING IN HEALTH INSURANCE BY NELSON- AALEN ESTIMATOR - Istikaanah, Najmah (AKSIOMA, 2011)
In this paper the using of Nelson Aalen estimators are presented to estimate transition probabilities of multistate model. Based on discrete time Markov, we will get transition matricesÂ  which the elements are transition probabilities from Nelson Aalen estimator. Because of the data that used in the construction of transition matrices are personâs health histories, then it can be seen as a morbidity value, which can be used to premium pricing.Â  Key words: Markov process, multistate model, Nelson Aalen, transition probability.